2022
DOI: 10.3171/2022.2.spine211576
|View full text |Cite
|
Sign up to set email alerts
|

Do the newly proposed realignment targets for C2 and T1 slope bridge the gap between radiographic and clinical success in corrective surgery for adult cervical deformity?

Abstract: OBJECTIVE Surgical correction of cervical deformity (CD) has been associated with superior alignment and functional outcomes. It has not yet been determined whether baseline or postoperative T1 slope (T1S) and C2 slope (C2S) correlate with health-related quality-of-life (HRQoL) metrics and radiographic complications, such as distal junctional kyphosis (DJK) and distal junctional failure (DJF). The objective of this study was to determine the impact of T1S and C2S deformity severity on HRQoL metrics and DJF dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…Many CD classifications have been proposed to address this issue, but the disassociation between these 2 prominent outcomes continues to riddle the spine surgeon. 22,27-30 Our study concluded NF patients demonstrated equivocal mean improvement in NDI by 2 years, despite experiencing the least amount of improvement in 2 of the 3 radiographic modifiers. Furthermore, they also had the highest rates of deterioration in the horizontal modifier by 2 years.…”
Section: Discussionmentioning
confidence: 69%
“…Many CD classifications have been proposed to address this issue, but the disassociation between these 2 prominent outcomes continues to riddle the spine surgeon. 22,27-30 Our study concluded NF patients demonstrated equivocal mean improvement in NDI by 2 years, despite experiencing the least amount of improvement in 2 of the 3 radiographic modifiers. Furthermore, they also had the highest rates of deterioration in the horizontal modifier by 2 years.…”
Section: Discussionmentioning
confidence: 69%
“…The patient's compensation to maintain a horizontal gaze may be represented by C2S. 11 Incremental inclination is represented by C2S, which reflects the need for more extension of the upper cervical spine. Thus, the capacity to extend the upper cervical spine is related to a patient's ability to maintain the horizontal gaze during cervical malalignment.…”
Section: Discussionmentioning
confidence: 99%
“…C2S presents a simplified understanding of cervical alignment and is suggested as a unified key to understanding cervical alignment relative to the thoracic spine. 11 OT, like PT, denotes the spatial orientation of the dens, which may vary according to the balance of the cranium and horizontal gaze. OI, like PI, is related to the compensatory reservoir of cervical extension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations